2004
DOI: 10.1021/jp031048c
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multiple-Pulse Experiments to Characterize Broad NMR Chemical-Shift Powder Patterns from Spin-1/2Nuclei in the Solid State

Abstract: The utility of the Carr-Purcell Meiboom-Gill (CPMG) experiment and a modified-CPMG experiment in characterizing NMR chemical-shift powder patterns for spin-1 / 2 nuclei is demonstrated. Heavier NMR-active nuclei such as 195 Pt, 199 Hg, and 207 Pb are known to be extremely sensitive to their local environment and as such have very large chemical-shift ranges. In the solid state, such nuclei commonly exhibit chemical shifts that range well over 1000 ppm, depending upon the orientation of the molecule within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 104 publications
7
100
1
Order By: Relevance
“…The signal-to-noise ratio was enhanced by acquiring the 29 Si signals via Carr−Purcell−Meiboom−Gill spin echo trains (REAPDOR-CPMG, see Figure 2). 31 The delay time τ for echo formation was set to 1.25 ms. To assess the extent of the dipolar dephasing, two experiments with recoupling times of 1.25 and 2.0 ms were done, coadding 2048 scans at a relaxation delay of 60 s. The saturation comb was used to start each acquisition with a reproducible stationary magnetization. Experimental conditions were optimized on a 29 Si-enriched glassy NaAlSiO 4 sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The signal-to-noise ratio was enhanced by acquiring the 29 Si signals via Carr−Purcell−Meiboom−Gill spin echo trains (REAPDOR-CPMG, see Figure 2). 31 The delay time τ for echo formation was set to 1.25 ms. To assess the extent of the dipolar dephasing, two experiments with recoupling times of 1.25 and 2.0 ms were done, coadding 2048 scans at a relaxation delay of 60 s. The saturation comb was used to start each acquisition with a reproducible stationary magnetization. Experimental conditions were optimized on a 29 Si-enriched glassy NaAlSiO 4 sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The experimental challenge of these measurements on heavy metals such as mercury arises from the typically large chemical-shift dispersion (often several thousands of parts per million) and long spin-lattice relaxation times [1,2]. One method of sensitivity enhancement that is often used in solid-state 199 Hg NMR studies is cross-polarization (CP) from abundant spins such as protons [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Direct polarization techniques, with their limitations, must be used to obtain these spectra. Another common technique to increase sensitivity in spectra of solids is magic-angle spinning (MAS) [1,2]. However, even that technique is of limited use, as the dipolar coupling between the spin-½ 199 Hg and the quadrupolar halide nucleus does not completely average to zero under MAS [6].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we and others have shown that the CPMG technique can give significant S/N enhancements for spin-1/2 nuclei having broad powder patterns, such as 109 Ag,113 Cd, 195 Pt, 199 Hg, and 207 Pb, while retaining anisotropic magnetic shielding information (47,48). In addition, the CPMG experiment may be used to partially remove homonuclear dipolar coupling; however, other techniques, such as the MW-4 (31,32) [see Fig.…”
Section: Application Of Multiple-pulse Spin-echo Experiments: Spin-1/mentioning
confidence: 99%
“…The step size must be chosen such that it is less than or equal to the excitation profile of the pulse and the total number of subspectra required depends on the breadth of the full spectrum. For Hg(CH 3 CO 2 ) 2 , a total of nine subspectra were necessary to obtain the full 199 Hg NMR spectrum (47). Two methods for constructing a single spectrum with an accurate lineshape from a series of subspectra are: variable offset cumulative spectra (VOCS) (59) or skyline projection (60).…”
Section: Figurementioning
confidence: 99%